MANUSIA KEI: RELASI-RELASI SEPUTAR KEMATIAN DI SEBUAH DESA DI KEPULAUAN KEI - Refo, Ignatius (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2012)
This study is an effort to know the real relations in a village on Kei Island. Using field study, I chose Lumefar village, a small village in the South of Kei Kecil Island. The society of Lumefar presents several fundamental relationships: tomat ohoi ratut explains internal relations in the village and tomat ohoi rivun explains external relations with other villages. All relations are important to show the specific background of Lumefar society itself and its world. The House (rahan) is an important social unit, which consists of families, united by the same name fam and descendants of the same ancestor. It is autonomous in the sense that each house is well organized under the leadership of the elder brother of the House.